1983
DOI: 10.1051/jphyscol:1983367
|View full text |Cite
|
Sign up to set email alerts
|

Raman Study of Doped Polyacetylenes

Abstract: Nous présentons les résultats de diffusion Raman obtenus sur des échantillons de polyacétylènes dopés soit avec des accepteurs d'électrons (I2, Br2, SDF5 , CIO4",FeClj), soit avec des donneurs d'électrons (Li par exemple). Nous montrons que l'isomérisation cis-trans est toujours induite, quel que soit le dopage effectué. Le dopage s'accompagne d'un raccourcissement des séquences trans (par rapport à un trans-(CH) x non dopé) si l'on admet le modèle des distributions de longueurs de chaînes. En plus, une bande … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Other areas such as the classification of disorder and extrinsic order in the polymer (182), particularly hydrogenated polyacetylenes (183), the cis isomer (184,185), and the results of using ultraviolet laser excitation (186), have also been reported. Studies on the effects of doping on this polymer and similar polymers have been reported, using both electron donors and acceptors as the doping agent (187)(188)(189)(190). Polyethylene has also been studied in some detail, and areas of interest include conformational studies (191), flowing melts (192), studies on orientation (193) and chain branching (194), and the correlation of structural data with longitudinal acoustic modes in polyethylenes (195,196).…”
Section: Polymersmentioning
confidence: 99%
“…Other areas such as the classification of disorder and extrinsic order in the polymer (182), particularly hydrogenated polyacetylenes (183), the cis isomer (184,185), and the results of using ultraviolet laser excitation (186), have also been reported. Studies on the effects of doping on this polymer and similar polymers have been reported, using both electron donors and acceptors as the doping agent (187)(188)(189)(190). Polyethylene has also been studied in some detail, and areas of interest include conformational studies (191), flowing melts (192), studies on orientation (193) and chain branching (194), and the correlation of structural data with longitudinal acoustic modes in polyethylenes (195,196).…”
Section: Polymersmentioning
confidence: 99%